Effect of ifrs compliance on the profitability of listed banks in ghana - NTOW ISAAC (KNUST, 2024)
A thesis submitted to the department of accounting and finance, school of business, college of humanities and social sciences Kwame Nkrumah university of science and technology, Kumasi, Ghana, in partial fulfillment of the requirements for the degree of master of science (accounting and finance)